Development of Civil Servants in Public Service at the West Kairatu Sub-district Office, West Seram Regency - Iriane Sosiawaty Ponto; Jeanly Waisapy; Zul Fadli (Universitas Padjadjaran, 2023)
This study analyzes the development of the Civil Servant Apparatus (ASN) in public service at the West Kairatu Sub-District Office, West Seram Regency. The research method is quantitative, utilizing a questionnaire instrument to collect data from the ASN at the office. The method of data analysis is quantitatively descriptive, and the research results are presented concisely for easy comprehension. The main focus includes work discipline, career development for ASN, and the application of ethical codes in public service. Work discipline is measured through attendance, strict rules aspect, and responsibility. The analysis results indicate